The trend of groundwater recharge in the secondary perched reaches of the Yellow River in the past 50 years - Zhang, Min; Ping, Jianhua; Mei, Xuemei; Leng, Wei; Li, He; Zhao, Jichang; Liu, Jiaqi (Frontiers in Environmental Science, 2023)
Precipitation infiltrates into the soil or river and then percolates downward through the deeper mineral soil to the groundwater. Understanding the interactions between surface water and groundwater in the river ecosystem is crucial for supporting decision-making in eco-construction and the efficient use of water resources. In our study, the secondary perched reach of the lower Yellow River was taken as the research area. The trend analysis and correlation relationship were evaluated using the M–K significance test and gray correlation; furthermore, the groundwater recharge was quantified by Darcy‘s law and the water balance method based on 50 years of hydrological data. The results showed that 1) from 1972 to 2020, the runoff and water level of the Huayuankou hydrological station and the Jiahetan hydrological station showed a significant downward trend. 2) The calculation of the gray correlation degree method shows that the groundwater level is mainly affected by the Yellow River. The river water and groundwater levels show a significant downward trend using the M–K significance test. 3) The unit width recharge values of the secondary perched river to the groundwater in the dry year were calculated to be 566.79 and 374.13 m3/m·d, using Darcy‘s law and the water balance method, respectively, indicating that the results of the two methods are basically the same. Our findings highlight the storage capacity of groundwater and can provide support for regulation and sustainable management of water resources in the ecosystem.